2021
DOI: 10.3390/ani11082309
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Probiotic Lactobacillus Supplementation Improves Liver Function and Reduces Cholesterol Levels in Jeju Native Pigs

Abstract: We evaluated the dietary effects of multiple probiotics in Jeju native pigs, using basal diet and multi-probiotic Lactobacillus (basal diet with 1% multi-probiotics) treatments (n = 9 each) for 3 months. We analyzed growth performance, feed efficiency, backfat thickness, blood parameters, hematological profiles, adipokines, and immune-related cytokines in pig tissues. Average daily gain, feed intake, feed efficiency, backfat thickness, and body weight were not significantly different between both groups. In La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Kim al. [45] found that cholesterol concentration was significantly decreased in the pigs fed with Lactobacillus-based probiotic. From this, it may be inferred that probiotic supplementation in weaning piglets improves the lipid profile by decreasing the TC and LDL concentration in serum and by increasing the HDLc concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Kim al. [45] found that cholesterol concentration was significantly decreased in the pigs fed with Lactobacillus-based probiotic. From this, it may be inferred that probiotic supplementation in weaning piglets improves the lipid profile by decreasing the TC and LDL concentration in serum and by increasing the HDLc concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Yu et al [49] found that selenium in combination with complex probiotics (Lactobacillus acidophilus, Lactobacillus pentose, and B. subtilis) tended to reduce TC, VLDL, and TG and increase HDLc concentrations in the blood. Kim et al [50] reported that the cholesterol concentration was significantly de-creased in pigs fed with Lactobacillus-based probiotic formulations. From this, it may be inferred that probiotic supplementation in weaning piglets can improve the lipid profile by decreasing the TC and LDL concentrations and increasing the HDLc concentration in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not fully understood how immune activation or tolerance is achieved in response to the probiotic bacteria, interactions between MAMPs and pattern recognition receptors (PRRs) of the host intestinal cells are involved (Liao and Nyachoti 2017 ). One such mechanism by which Lactobacillus -based probiotics suppress inflammation has been suggested to be initiated by TLR2 (Peng et al 2022 ; Wang et al 2019a ), TLR4 (Peng et al 2022 ; Tang et al 2021 ; Yi et al 2018 ), or NOD1 activation (Kim et al 2021 ) through NF-κB or MAPK signaling pathways in the jejunum and ileum of pigs. Thereafter, the recognition of probiotic antigens leads to regulations of cell-mediated immune responses in the porcine intestine.…”
Section: Alternatives To Antibiotics In Pig Production: Modulating Th...mentioning
confidence: 99%